Caracterización de la tapiza en fibra poliester, para su reutilización como sustrato agrícola (2013)
This project was undertaken to respond to environmental problems generated in the auto parts industry, from fiber composite polyester / primer / polyethylene used in the manufacture of upholstered car. Above, because the carpet to conform to the production of the lining of the automobile, it generates a 33% by weight of waste material from the die. Said waste is hardly usable as their size and geometry is not uniform. Furthermore, the chemical differences of its components make it impossible to reprocess from heat, the chemical decomposition of solvents is expensive and it is also environmentally negative and incineration or energy recovery generates fumes and suspended solids, which also are contaminants.